The induction of experimental sinusitis in rabbits and the place of bromhexine as a mucolytic nose drop in the treatment of sinusitis - Koyuncu, M.; Yilmaz, M.; Yalcin, S.; Metin, N.; Gunduz, S.; Karadas, E. (My University, 1990)
[Abstract Not Available]
Keywords: bromhexine; animal experiment; animal model; article; controlled study; drug efficacy; intranasal drug administration; nonhuman; rabbit; sinusitis